2019
DOI: 10.3390/cancers11101420
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies in Dermatooncology—State of the Art and Future Perspectives

Abstract: Monoclonal antibodies (mAbs) targeting specific proteins are currently the most popular form of immunotherapy used in the treatment of cancer and other non-malignant diseases. Since the first approval of anti-CD20 mAb rituximab in 1997 for the treatment of B-cell malignancies, the market is continuously booming and the clinically used mAbs have undergone a remarkable evolution. Novel molecular targets are constantly emerging and the development of genetic engineering have facilitated the introduction of modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 289 publications
(318 reference statements)
0
5
0
Order By: Relevance
“…55 It is not yet sufficiently elucidated if in the setting of a tumor arising in T cells themselves, PD-1 blockade strengthens more antitumor T cell immunity or rather facilitates tumor progression. 50,[56][57][58][59][60] We evaluated the impact of PD-1 blockade (nivolumab 10 µg/mL) on T cell proliferation by measuring non-radioactive 5-bromo-2ʹ-deoxyuridine (BrdU) incorporation. PD-1 blockade resulted in enhanced proliferation of T cells upon stimulation; however, we observed the strongest enhancement of proliferation within the fraction of the clonal tumor T cell as compared to their benign non-clonal counterparts ( Figure 6).…”
Section: Pd-1 Blockade Reduces Th2 Phenotype Of Non-tumoral Bystandermentioning
confidence: 99%
“…55 It is not yet sufficiently elucidated if in the setting of a tumor arising in T cells themselves, PD-1 blockade strengthens more antitumor T cell immunity or rather facilitates tumor progression. 50,[56][57][58][59][60] We evaluated the impact of PD-1 blockade (nivolumab 10 µg/mL) on T cell proliferation by measuring non-radioactive 5-bromo-2ʹ-deoxyuridine (BrdU) incorporation. PD-1 blockade resulted in enhanced proliferation of T cells upon stimulation; however, we observed the strongest enhancement of proliferation within the fraction of the clonal tumor T cell as compared to their benign non-clonal counterparts ( Figure 6).…”
Section: Pd-1 Blockade Reduces Th2 Phenotype Of Non-tumoral Bystandermentioning
confidence: 99%
“…Of note, although injections of mice are performed with 20 micrograms of RNA per injection, this formulation was previously demonstrated by Kranz et al to be efficacious at a similar dose (7.2 to 29 micrograms) per injection in humans [ 12 ]. This type of vaccination can be advantageously combined with immune checkpoint inhibitors currently under evaluation in T-lymphomas [ 37 , 38 , 39 , 40 ] or established immunomodulatory approaches, especially interferon-alpha [ 41 , 42 ]. The possibility of vaccinating against the TCR to treat CTCL is further supported by other reports: Berger et al [ 43 ], Zheng et al [ 44 ] and Winter et al [ 45 ] have shown that MHC class I epitopes derived from TCR chains expressed in human CTCL can be recognised by cytotoxic T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that iHDACs might be helpful in overcoming HLA class-I expression loss in PD-1/PD-L1 non-responder patients ( 77 ). In summary, histone acetylation dysregulation in chief immune system players represents a key mechanism whereby MCC can escape the anti-tumor response, while expression restoration in immune regulatory complexes by iHDACs epigenetic priming might be a helpful therapeutic approach based on boosting adaptive immune responses ( 38 ).…”
Section: Histone Post-translational Modifications and Merkel Cell Car...mentioning
confidence: 99%
“…The use of Programmed cell death protein 1 (PD-1) and Programmed death-ligand 1 (PD-L1) inhibitors seems to be an effective therapeutic approach (33)(34)(35)(36). Novel therapies are also under evaluation (31,(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%